CONTRIBUTION OF THE IMPLEMENTATION OF RELIGIOUS MODERATION TOWARDS THE ACHIEVEMENT OF PAI LEARNING AT STATE ELEMENTARY SCHOOL 054913 PALUH PAKIH - Supratman (Journal of Quality Islamic Education Research, 2024)
This study describes how the implementation of religious moderation and the formation of a tolerance attitude in Islamic Religious Education learning is carried out at SD Negeri 054913, The research method used in this study is Qualitative Descriptive Analysis. The collection of research data was obtained by observation, interview and documentation study techniques. The steps of data analysis are by collecting data, reducing data, presenting data and concluding data. To test the validity of the data, an examination technique is needed. The implementation of the examination technique is based on four criteria, namely: credibility, transferability, dependability, confirmability.This study found: (1). Learning planning was carried out when compiling the syllabus, material on religious moderation and Tasamuh attitudes was inserted into the Islamic Religious Education material. At the planning stage, teachers also coordinated with the principal who provided encouragement to Islamic Religious Education subject teachers in forming student character and realizing religious moderation and Tasamuh attitudes in the scope of  054913 (2). The implementation of learning was carried out using appropriate learning methods in this case with the lecture method, and discussions, both direct discussions and group discussions, and this aims to instill a moderate attitude in students, namely respecting each other, respecting, being fair to group friends, and being sporty during learning (3). The implementation of religious moderation and tasamuh attitudes in State Elementary School 054913 through Islamic Religious Education learning has been seen in changes in students' attitudes, namely students have very good religious attitudes and social attitudes such as, obeying worship, respecting others, establishing intimacy, having social concern, having a nationalist spirit, being tolerant, and obeying the rules.